2019
DOI: 10.1111/jar.12610
|View full text |Cite
|
Sign up to set email alerts
|

Progressive resistance training for persons with intellectual disabilities and visual impairment

Abstract: Background Knowledge concerning the feasibility and effects of progressive resistance training (PRT) for persons with intellectual disabilities and visual impairment who are categorized in Gross Motor Function Classification System (GMFCS) Level 1 is limited. The aim of our study was to evaluate feasibility and effect of PRT on participants' Quadriceps strength and personal goals. Methods Eight Participants followed a PRT program for 10 weeks. Feasibility was determined by percentage of attendance and complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Several studies have reported that RT improves muscle strength in both adults [8] and adolescents [9] with ID. However, whether this improvement transfers to improved work task performance has received less attention in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that RT improves muscle strength in both adults [8] and adolescents [9] with ID. However, whether this improvement transfers to improved work task performance has received less attention in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, resistance training (RT) has received much less attention in this population despite the beneficial effects of muscle strength on functional tasks of daily living and employability in adults with DS [8,9]. In a recent study, a 12-week circuit RT program significantly reduced oxidative damage by increasing antioxidant enzyme activity in young adults with DS [10].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle‐strength and flexibility training can be used to help ID children reinforce core strength, coordinate the lower limbs and improve posture control ability (Smith et al ., 2007). For uncoordinated bilateral lower limb development, the training priority is to improve the disadvantaged limb's muscle strength and joint flexibility using standing and squatting calf raises, weight‐bearing single‐support training and resistance training (Dijkhuizen et al ., 2019). Non‐standard postures, like excessive ankle internal or external rotation, are usually caused by lower calf muscle strength and abnormal calf muscle tone (Cao et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the common use of GAS in clinical practice and in research, confidence in the results of studies using this method can be low because of the great variability in how researchers apply it (Krasny-Pacini et al, 2016). Furthermore, there is a lack of studies attempting to use GAS to facilitate individual goal setting and to describe individual goals for adults with PIMD in relation to participation in existing or new activities in everyday life (Dijkhuizen et al, 2019;Jones et al, 2006;Nguyen et al, 2019;World Health Organization, 2001). Jones et al conducted a study including persons with PIMD where GAS goals were set in areas of potential improvement including access to community-based experiences, but most goals were related to behaviour, health and physical competence.…”
Section: What This Paper Addsmentioning
confidence: 99%